Antibacterial activities of Aspergillus fumigatus SSH01 crude extracts - Radzali, Mohamad Khairil (2016)
Antimicrobial agents are mainly derived from natural products. The scientific evidence for the various antimicrobial activities from thermotroph, as referred here,thermotolerant Aspergillus fumigatus SSH01 is scarce and fragmented. Additionally,bacterial resistance to antibiotics is a public health problem that is increasing around the globe which later complicated illnesses.Therefore, the main objective of this study was to determine the antibacterial activities of fungal crude extracts and to investigate the modes of action of the extracts against susceptible pathogens. Methanol was used to extract metabolites from A. fumigatus SSH01 by submerged fermentation. The extract was investigated for its antimicrobial properties against pathogenic Gram-positive bacteria (methicillin-resistant Staphylococcus aureus S547, Staphylococcus aureus ATCC 6538, Bacillus subtilis ATCC 6633 and Listeria monocytogenes L10) and pathogenic Gram-negative bacteria (Escherichia coli ATCC 8739, Escherichia coli 0157: H7 E187, Salmonella enterica serovar Thypimurium S836 and Pseudomonas aeruginosa ATCC 15442) as well as yeast, Candida albicans ATCC 10231 using disc diffusion method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the extract were determined by broth microdilution method. Time-killing kinetics, scanning electron microscopy (SEM), and detection of cellular leakage of proteins and 260nm absorbing-compounds of susceptible Gram-positive pathogens were determined after exposure of bacterial cells to three concentrations (1/2, 1, and 2MIC) of 100% of methanolic crude extracts. The methanolic extract exhibited zone of inhibition ranged from 11.00 mm to 18.00 mm.The MIC values ranged from 0.097 mg/ml to 12.50 mg/ml whereas the MBC values ranged from 0.195 mg/ml to 25 mg/ml. The growth of all treated test microorganisms were inhibited at the concentration of twice MIC values in time-kill assay. Average log reduction of bactericidal effects (MIC and 2MIC) in viable cell count ranged from 7.75 Log10 to 5.52 Log10 CFU/ml and between 7.72 Log10 to 6.36 Log10 CFU/ml in MIC and 2MIC of the extracts, respectively. Detection of cellular leakage of proteins (595nm) and 260nm absorbing-compounds showed slightly increased to the time of exposure of cells to the extracts and suggesting its ability to damage the bacterial membrane. In addition,scanning electron micrograph (SEM) demonstrated disruption in morphology of the treated cells. Liquid chromatography/time-of-flight/mass spectrophotometry (LC/TOFMS) was used to analyze the constituents of the extracts. Six metabolites were identified included L-tyrosine, kojic acid, fumagillin, fumigaclavine B, helvolic acid and citrinin. In MTT assay, SSH01 crude extract was found to be cytotoxic against HaCat with IC50 of 20 mg/ml and 0.78 mg/ml after 24 and 48 h of treatment. Further studies maybe required to explain the risk of toxicity (kojic acid and citrinin) of the crude extracts and its stability for the application of human use. The constituents of the extracts should also be isolated,identified,characterized perhaps improvise for better potential as antibacterial drugs.